Determinants of Social and Environmental Reporting Practices Disclosure in Libyan Oil and Gas Industry: A Managerial Perspective - Omar, Mohammed Mispah Said; Echchabi, Abdelghani; Ayedh, Abdullah Mohammed; Al-Hajri, Salim (International Journal of Energy Economics and Policy, 2021)
The purpose of the study is to investigate the management behaviour in reporting CSER activities and the factors that influence their decision behaviour in the case of Libyan Oil and Gas industry. For this purpose, in-depth interviews were conducted with 9 managers working in Oil and Gas industry in Libya. The transcribed interviews were then analyzed using thematic approach. The findings revealed that the managers recognize companies’ social and environment responsibility, on a self-motivation basis as well as due to the potential negative impacts of a company’s operations on the environment and society. On the other hand, the oil and gas companies deem themselves obliged to report their CSER practices due to the increased awareness about the potential negative impacts of the oil and gas industry. Nevertheless, the disclosure of these practices is still limited due to the lack of a comprehensive framework that sets all CSER requirements for Libyan companies. It is noteworthy that this is the first study that focuses on the management behavior in reporting CSER activities in the Libyan oil and gas industry. Hence, it makes a great contribution and lays the foundation for the future studies in the CSER area. Keywords: Social and Environmental Reporting, Managerial Perception, Developing Economies, Oil and Gas Industry JEL Classifications: Q43, Q52, Q54, M14, L71 DOI: https://doi.org/10.32479/ijeep.10821